Impacts of COVID-19 pandemic restrictions on socio- economic conditions of smallholder livestock farmers in Kelantan - Nur Syuhada Sazali (2022)
During the COVID-19 pandemic, Malaysia has implemented the movement control order (MCO) on 18 March 2020, and then it was extended several times. As a result, all economic, social and agricultural activities were entirely halted. The livestock sector supports the livelihood of rural communities in Malaysia, because animal products represent an important protein source. Therefore, this study was conducted to understand the operating situation and demands of smallholder livestock farmers affected by the COVID-19 pandemic. The survey was carried out by two rounds in 10 districts of Kelantan. The first round of survey was conducted between September and November 2020, and the second round was conducted between November to December 2021. The data was collected using a pre-tested questionnaire that were addressed mainly about: farmers’ basic information, farm management, marketing and action taken during COVID-19. Each interview was conducted face to face only after the given consent of the respondents to attend the interview and was strictly followed the standard operating procedure (SOP) of COVID-19. The descriptive statistics were used for data analysis. A total of 111 smallholder livestock farmers joined in this survey (89% of respondents were male; 31% of respondents were <30 years old; and 70% of respondents were education from secondary school). Results showed that about 72%, 11%, 10% and 4% of respondents were small landholdings (<2 ha), medium landholdings (>2 ha - 4 ha), large landholdings (≥5 ha) and landless (0 ha) farmers, respectively. There was no significant (p>0.05) difference on monthly income among the various landholding categories of farmers. Nearly all (94%) of the respondents were able to purchase feed, and 59% of respondents collected fodder from their surroundings during the MCO. Moreover, the majority (74%) of respondents did not acquire treatments for their animals., and 52% of respondents had lost animals on their farms. The majority (81%) of respondents claimed to be capable of rearing livestock on their own, implying that they do not need to employ the manpower during the MCO. The findings also revealed that farmers' business outputs have changed, including decreased products demand (56% of respondents) and experiencing a lower income (50% of respondents). However, about 48% of the respondents claimed that they were less affected by the marketing channel, and they were able to sell their animal products during the MCO. Despite all the challenges and difficulties, about half (48%) of the respondents claimed a steady market price trend, while more than 20% of the respondents were claimed a decreasing and increasing trend in market price during the COVID-19 pandemic. In conclusion, the COVID-19 pandemic had a less significant impact on the socio-economic conditions and livelihoods of smallholder livestock farmers in Kelantan due to the various coping strategies implemented by Malaysian government. Some recommendations have been made to ensure the livestock sector's continuity and sustainability, and they can be applied to other sectors and countries with similar economic issues.